Problematika Pembinaan Keagamaan Siswa di SMP Negeri 8 Palangkaraya - Risnawati Risnawati; Muslimah Muslimah; Surawan Surawan (Kuttab: Jurnal Ilmu Pendidikan Islam, 2025)
Religious education is an integral part of the curriculum that guides students in developing morality, ethics, and spiritual values. This study aims to examine the challenges of religious guidance at SMPN 8 Palangka Raya. The research employed a descriptive-qualitative method with data collected through observation, interviews, and documentation. The subjects of the study were Islamic Religious Education teachers and students at SMPN 8 Palangka Raya. The findings reveal that religious guidance activities include spiritual counseling, social development, and cultural programs. However, several challenges were identified in the implementation process, including time constraints, limited external environmental support, and low student interest. This study is expected to provide insights and practical recommendations for schools, particularly teachers, in formulating more effective and innovative strategies for religious education.